A merry little meet cute : a novel [large type] - Murphy, Julie, 1985-; Simone, Sierra (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
"Cowritten by #1 New York Times bestselling author Julie Murphy and USA Today bestselling author Sierra Simone--a steamy plus-size holiday rom-com about an adult film star who is semi-accidentally cast as a lead in a family-friendly Christmas movie, and the former bad-boy pop star she falls in love with"--